Implementing Individual Producer Responsibility for Waste Electrical and Electronic Equipment through Improved Financing. (10th October 2012) - Mayers, Kieren; Lifset, Reid; Bodenhoefer, Karl; Van, Luk N.
Summary Under the European Union (EU) Waste Electrical and Electronics Equipment (WEEE) Directive, producers are responsible for financing the recycling of their products at end of life. A key intention of such extended producer responsibility (EPR) legislation is to provide economic incentives for producers to develop products that are easier to treat and recycle at end of life. Recent research has shown, however, that the implementation of EPR for WEEE has so far failed in this respect. Current WEEE systems calculate their prices according to simple mass‐based allocation of costs to producers, based on broad collection categories containing a mixture of different product types and brands. This article outlines two alternative approaches, which instead calculate charges for products sold by producers by classifying them according to their eventual end‐of‐life treatment requirements and cost. Worked examples indicate that these methods provide both effective and efficient frameworks for financing WEEE, potentially delivering financial incentives to producers substantial enough to affect their potential profitability and, as a likely consequence, the decisions relating to the design of their products. In particular they fulfill three important criteria required by the WEEE Directive: they can financially reward improved design, allocate costs of historic waste proportionately (on the basis of tonnes of new products sold), and provide sufficient financial guarantees against future waste costs and liabilities. They are also relatively practical for implementation because they are based solely on cost allocation and financing. Further research and investigation would be worthwhile to test and verify this approach using real‐world data and under various scenarios.